Scaling Up Early Childhood Education: A Foundation for Long-Term Educational Success in Ethiopia - Goshu, Belay Sitotaw; Ridwan, Muhammad (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2012)
The quality of early childhood education in Ethiopia faces significant challenges, particularly related to teacher training, resource availability, and parental involvement. This study aims to explore the key challenges in the Ethiopian early childhood education system and assess their impacts on both teacher effectiveness and student learning outcomes. The research employed a mixed-methods approach, combining quantitative data from surveys with qualitative interviews. Twenty education officials were interviewed to gather in-depth insights, and 200 instructors from various regions participated in the survey. Exploring the requirement for teacher training, determining the availability of resources, comprehending teacher motivation, analyzing the connection between class size and learning quality, and exploring the influence of parental engagement are the study's five main goals. The findings show a severe lack of educational resources and inadequate teacher preparation in rural areas. Additionally, learning outcomes were found to be adversely affected by large class sizes, and student achievement was significantly correlated with parental participation. The results emphasize the necessity of focused measures to close these inequalities, including bettering teacher preparation programs, allocating more funds, lowering class sizes, and encouraging family involvement in education. Tackling these issues will help Ethiopia's early childhood education level rise and promote a more efficient and equitable educational system.